Exploring breastfeeding patterns and barriers in a Kerala tertiary care hospital: a cross-sectional study - Suresh, Ananthakrishnan; K., Jino Joseph; Simethy, Mary Andrea (International Journal of Contemporary Pediatrics, 2024)
Background: Exclusive breastfeeding is vital for maternal and child health, yet challenges persist. This study in a Kerala tertiary care hospital aimed to assess prevalence, identify barriers, and explore cultural influences. Aim was to determine the prevalence of exclusive breastfeeding, uncover the barriers mothers face, and explore cultural factors affecting infant feeding choices. Methods: Utilizing Google forms, 274 postpartum women were surveyed. Participants provided data on awareness, practices, challenges, and factors influencing their infant feeding choices. Results: While 94.9% were aware of the ideal breastfeeding duration, only 74.1% practised exclusive breastfeeding until six months. Inadequate breast milk, sore nipples, and family pressure emerged as challenges. The timing of solid food introduction significantly impacted exclusive breastfeeding. Conclusions: Our study offers insights into exclusive breastfeeding practices. Culturally sensitive interventions, comprehensive support systems, and healthcare provider engagement are crucial. This study echoes recent research, emphasizing the multifaceted nature of exclusive breastfeeding practices, calling for diverse and context-specific strategies to empower mothers and ensure infants receive the best nutritional start.